Systematic Literature Review: Validitas Prognostik NIHSS sebagai Prediktor Luaran Fungsional pada Pasien Stroke (Tinjauan Periode 2020–2025) - Naomi Elfriede Sirait; TA Larasati; Laisa Azka; Fitria Saftarina (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
The National Institutes of Health Stroke Scale (NIHSS) is the standard instrument for stroke evaluation, yet its prognostic validity for functional outcomes continues to evolve with the shift from static to dynamic assessment. This systematic review aims to evaluate the prognostic validity of NIHSS (static vs. dynamic) and the influence of lesion location and biological factors on functional outcome prediction accuracy in global and Indonesian literature from 2020–2025. A Systematic Literature Review (SLR) design was employed following PRISMA 2020 guidelines. Searches were conducted across five databases (PubMed, Scopus, Web of Science, Garuda, ISJD) using keywords related to NIHSS and prognosis. Following rigorous selection, 20 articles (10 global, 10 Indonesian) were included for narrative synthesis. Data synthesis demonstrated the superiority of